Structural Modification of the Antidepressant Mianserin Suggests That Its Anti-inflammatory Activity May Be Independent of 5-Hydroxytryptamine Receptors - Sacre, Sandra; Jaxa-Chamiec, Albert; Low, Caroline M. R.; Chamberlain, Giselle; Tralau-Stewart, Cathy (Frontiers in Immunology, 2019)
Antidepressants are increasingly recognized to have anti-inflammatory properties in addition to their ability to treat major depressive disorders. To explore if engagement of 5-hydroxytryptamine (5-HT) receptors was required for the anti-inflammatory effect of the tetracyclic antidepressant mianserin, a series of structural derivatives were generated with the aim of reducing 5-HT receptor binding. Primary human peripheral blood mononuclear cells were used to screen for anti-inflammatory activity. The lead compound demonstrated a significant loss in 5-HT receptor binding, as assessed by non-selective 5-HT binding of radiolabelled serotonin in rat cerebral cortex. However, it retained the ability to inhibit endosomal toll-like receptor 8 signaling in primary human macrophages and spontaneous cytokine production from human rheumatoid synovial tissue equivalent to that previously observed for mianserin. These data demonstrate that the anti-inflammatory mechanism of mianserin may be independent of 5-HT receptor activity. This research offers new insights into the mechanism and structural requirements for the anti-inflammatory action of mianserin.